Інженерне проєктування енергоефективного ножа кутера для закладів ресторанного господарства та харчової індустрії - Дуб, Володимир Васильович; Лебединець, Ігор Володимирович; Дмитревський, Дмитро В'ячеславович; Задорожня, Лариса Михайлівна; Стефашкіна, Анастасія Сергіївна; Dub, Volodymyr; Lebedynets, Igor; Zadorozhnia, Larysa; Stefashkina, Anastasia (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто актуальну проблему підвищення енергоефективності кутерного обладнання для харчової індустрії та рсторанного господарства. Встановлено, що енерговитрати залежать від кута загострення та профілю різальної кромки ножів. Оптимізація їх геометричних параметрів дає компроміс між зносостійкістю та питомими витратами. Запропоновано технічне рішення з метою зниження енергоспоживання приводу кутера. Розроблена конструкція ножа зменшує опір різанню та тепловиділення, а також запобігає нагріванню сировини понад норми. Наукова новизна отриманих результатів заключається у раціональному поєднанні елементів різальної кромки та форми корпусу ножа, що дозволяє знизити гідродинамічний опір під час роботи. Практична цінність розробки полягає у зменшенні експлуатаційних витрат. На запропоноване технічне рішення подано заявку на корисну модель. /// EN: This study addresses improving energy efficiency in cutter equipment for the food industry. A significant share of energy consumption during comminution is attributed to cutting resistance and friction between knife lateral surfaces and raw material. Geometric characteristics of cutting tools – sharpening angle, blade profile, and cutting edge configuration – directly impact energy expenditure and product quality. A review of scientific and patent literature shows that optimal selection of knife geometry allows a trade-off between tool wear resistance, specific energy consumption, and processed meat quality. However, existing designs (serrated or crescent-shaped knives) fail to simultaneously meet requirements of energy efficiency, reduced heat generation, and straightforward maintenance. The primary goal is to enhance energy efficiency of meat raw material comminution through a novel cutting tool with optimized geometry. The key objective is to lower specific energy consumption without compromising tool durability or process quality. Research methodology included analytical review, systematic analysis of knife geometry influence on energy performance, technological calculations, and engineering creativity methods. As a result, an original cutter knife design is proposed. The developed solution incorporates a multi-level serrated cutting edge with variable tooth pitch together with inclined perforations in the knife body. The serrated pattern ensures distributed cutting action, reducing resistance from connective tissues. Inclined holes decrease contact area, lowering friction, while perforation edges act as additional micro-cutting surfaces. The blade features an asymmetric cross-section – wavy on one side, flat on the opposite – simplifying sharpening and maintenance. Scientific novelty lies in the rational combination of the main cutting edge with auxiliary elements (serrated profile and perforation edges), reducing mechanical energy converted into heat. This prevents undesirable heating of raw material beyond technological limits and ensures lower hydrodynamic resistance. Practical value consists in reducing energy consumption of the cutter drive while maintaining finished product quality. The flat support surface enables convenient restoration of cutting properties under industrial conditions. A utility model application (No. u202504982 dated October 13, 2025) has been filed for the proposed design. Optimizing cutter knife geometry through a multi-level serrated edge and inclined perforations reduces cutting resistance, minimizes friction, and lowers heat generation. The proposed solution improves energy efficiency and reduces operational costs.
Design of an energy-efficient cutter knife for restaurants and the food industry
Keywords: різальний інструмент; подрібнення; тертя; тепловиділення; енергоефективність; зносос- тійкість; корисна модель; cutting tool; comminution; friction; heat generation; energy efficiency; wear resistance; utility model